Multiorgan Development of Oxidative and Nitrosative Stress in LPS-Induced Endotoxemia in C57Bl/6 Mice: DHE-Based In Vivo Approach. (22nd May 2019) - Proniewski, Bartosz; Kij, Agnieszka; Sitek, Barbara; Kelley, Eric E.; Chlopicki, Stefan
Abstract : Detection of free radicals in tissues is challenging. Most approaches rely on incubating excised sections or homogenates with reagents, typically at supraphysiologic oxygen tensions, to finally detect surrogate, nonspecific end products. In the present work, we explored the potential of using intravenously (i.v.) injected dihydroethidine (DHE) to detect superoxide radical (O2 ∙- ) abundance in vivo by quantification of the superoxide-specific DHE oxidation product, 2-hydroxyethidium (2-OH-E + ), as well as ethidium (E + ) and DHE in multiple tissues in a murine model of endotoxemia induced by lipopolysaccharide (LPS). LPS was injected intraperitoneally (i.p.), while DHE was delivered via the tail vein one hour before sacrifice. Tissues (kidney, lung, liver, and brain) were harvested and subjected to HPLC/fluorescent analysis of DHE and its monomeric oxidation products. In parallel, electron spin resonance (EPR) spin trapping was used to measure nitric oxide ( ∙ NO) production in the aorta, lung, and liver isolated from the same mice. Endotoxemic inflammation was validated by analysis of plasma biomarkers. The concentration of 2-OH-E + varied in the liver, lung, and kidney; however, the ratios of 2-OH-E + /E + and 2-OH-E + /DHE were increased in the liver and kidney but not in the lung or the brain. An LPS-induced robust level of ∙ NO burst was observed in the liver, whereas the lung demonstrated a moderate yet progressive increase in the rate of ∙ NO production. Interestingly, endothelial dysfunction was observed in the aorta, as evidenced by decreased ∙ NO production 6 hours post-LPS injection that coincided with the inflammatory burden of endotoxemia (e.g. elevated serum amyloid A and prostaglandin E2 ). Combined, these data demonstrate that systemic delivery of DHE affords the capacity to specifically detect O2 ∙- production in vivo . Furthermore, the ratio of 2-OH-E + /E + oxidation products in tissues provides a tool for comparative insight into the oxidative environments in various organs. Based on our findings, we demonstrate that the endotoxemic liver is susceptible to both O2 ∙- -mediated and nonspecific oxidant stress as well as nitrosative stress. Oxidant stress in the lung was detected to a lesser extent, thus underscoring a differential response of liver and lung to endotoxemic injury induced by intraperitoneal LPS injection.